An empirical validation of consumer video game engagement: A playful-consumption experience approach - Abbasi, A.Z. (2019)
This study proposes and validates a conceptual model for predicting consumer video game engagement, comprising cognitive, affective, and behavioural engagement originating from the imaginal, emotional, and sensory playful-consumption experience. To validate the conceptual model, data were collected from 465 teen video game consumers; 436 were useable. This study employed the WarpPLS 5.0 software to perform the Partial Least Squares-Structural Equation Modelling (PLS-SEM) analysis. The results of the measurement model on playful-consumption experience and consumer video game engagement support that both imaginal and emotional experience and cognitive, affective and behavioural engagement were reliable and valid as second-order formative constructs. Moreover, the findings of the structural model support that playful-consumption experiences such as imaginal, emotional, and sensory experience positively influence the prediction of cognitive, affective and behavioural states of consumer video game engagement. This study pioneers the field of digital game studies that have empirically validated a conceptual model predicting multiple states of the player's engagement in video game playing that is triggered through various playful experiences of a digital game. Â© 2018 Elsevier B.V.